Caffeine enhances some aspects of physical performance in well-trained hammer and discus throwers - Gallo-Salazar, C.; Del Coso, J.; Lara, B.; Aguilar-Navarro, M.; Giráldez-Costas, V.; Areces, F.; Revuelta, C.; Gutiérrez-Hellín, J.; Salinero, J. J. (Nutrients, 2024)
Background: Caffeine is a widely recognized ergogenic aid for enhancing exercise performance. However, its effect on throwing performance has been less studied, yielding contradictory results. Objectives: The main aim of the study was to analyze the potential ergogenic effects of a moderate dose of caffeine (3 mg·kg-1 body mass) on vertical jump performance and throwing distance during a simulated competition in trained discus and hammer throwers.